The role of media in establishing security and stability in Algeria Electronic Media as a model - larguet, hocine (Journal of Social Sciences and Humanities, 2021)
The changes that occurred in the economic, political and technical fields around the world have brought many advances in the media in general which affected the ways and methods of presenting news in terms of performance and orientation. This affected the traditional media which was followed by many researches concerning media and communication for years .We have to show the role of the responsive electronic system in the new field of media that describes new channels to tackle information and the methods of benefiting from it in reality since the open field of media is influenced by the changes that happened in this field in modern world .No one can deny the important role that media plays either it was modern or traditional in promoting a culture of peace and stability and even to face the dangers of terrorism .In this study we relied on the descriptive and analyzing method in order to analyze the the contribution of the electronic media in leading Algeria to safety and promoting a culture of peace and stability among people .This study showed the importance of electronic media in comparison to traditional one and the big role that social media plays in society as a modern and advanced means of communication rather than newspapers .This appeared in the Algerian experience in fighting terrorism.